2018
DOI: 10.3390/su10072255
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance Factors of Appropriate Technology: Case of Water Purification Systems in Binh Dinh, Vietnam

Abstract: This study selects a case involving water purification systems in Binh Dinh, Vietnam, as an appropriate example to examine appropriate technology (AT) acceptance factors and derive possible insights into the stable settlement and development processes whereby to diffuse AT. This analysis administered questionnaires to users of water purification systems installed in five elementary and middle schools in Binh Dinh, from which 296 samples were collected for the final analysis. The original unified theory of acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
1
13
0
3
Order By: Relevance
“…Therefore, performance expectations affect the different characteristics of information systems, which will benefit consumers. For example, Jaradat [57] and Lee [58] reported that performance expectations are essential predictors of willingness to use mobile commerce. Current evidence suggests that PE is essential to the application of m-payment [9,59,60].…”
Section: Hypothesis 4b (H4b) User Satisfaction Positively Affects Usmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, performance expectations affect the different characteristics of information systems, which will benefit consumers. For example, Jaradat [57] and Lee [58] reported that performance expectations are essential predictors of willingness to use mobile commerce. Current evidence suggests that PE is essential to the application of m-payment [9,59,60].…”
Section: Hypothesis 4b (H4b) User Satisfaction Positively Affects Usmentioning
confidence: 99%
“…The results showed that UTAUT perfectly matched the data. Lee et al [58] revealed the moderating effect of the government's role on the determinants of usage intention in the UTAUT model. According to this literature, we statistically tested the moderating effect of the different nationalities of consumers in the UTAUT model.…”
Section: Hypothesis 4b (H4b) User Satisfaction Positively Affects Usmentioning
confidence: 99%
“…Starting from the initial UTAUT model, the specialists tried to develop it by creating what is called UTAUT 2 by using other variables in addition to the four variables presented above. Thus, the specialists also used: delivery efficiency, cost-saving efficiency, online shopping experience in online commerce [32], quality of systems and quality of services in making payments through mobile telephony services by integrating UTAUT, the information systems success model (D&M ISS), and the task-technology fit model (TTF) [33]; hedonic motivation, familiarity with the concept of carsharing and emerging electric carsharing in the case of passengers on electric means of transport in China [34]; information quality, habitat (habit) in the case of food delivery through e-commerce computer applications [35]; hedonic motivation, the orientation to save prices, the habit of searching and booking restaurants using computer applications [36]; physical support and educational support for water purification systems [37]; habituation and demography in the case of integrating sustainability values (SV), theory of planned behavior (TPB), and UTAUT2 in the case of studying the options of travelers interested in sustainable hosting business [38].…”
Section: Hypothesis 4 (H4) Facilitating Conditions Affects the Intention To Use The Accounting Platformmentioning
confidence: 99%
“…To carry out the study, we apply the conceptual framework of the Unified Theory of Acceptance and Use of Technology (UTAUT), a theory widely used to explain why some individuals are more or less prone to adopt information technology of diverse types in their work environment [23,24]. UTAUT was introduced by Venkatesh et al (2003) [6], and it was inspired by eight previous theories that, to certain extent, explain technology usage: The Diffusion of Innovation Theory [25], The Theory of Reasoned Action [3], The Technology Acceptance Model [4], The Theory of Planned Behaviour [5], Social Cognitive Theory [26], Expectancy Confirmation Theory [27], The Model of Personal Computing Utilization [28], and the Motivational Model [29].…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%
“…The authors theorize that gender, age, experience, and degree of willingness moderate the hypothesized relationships. This unified model explained approximately 70% of the variance in behavioral intention, a value for which UTAUT has been widely used in different research related to diverse technologies and contexts [23,[30][31][32][33]. The robustness of the UTAUT model makes it a good theory to explain ERP system adoption at work, considering the personality type of users.…”
Section: Unified Theory Of Acceptance and Use Of Technology (Utaut)mentioning
confidence: 99%